1992
DOI: 10.3181/00379727-199-43356a
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Steroid Hormone Action in Target Cells by Specific Hormone-Inactivating Enzymes

Abstract: The target cell sensitivity of steroid hormones is determined by the concerted action of specific hormone receptors and steroid-inactivating enzymes. In recent years, a considerable amount of knowledge has been obtained on hormone receptor concentration-based target cell sensitivity. However, an equal understanding of the role of specific steroid-inactivating enzymes in hormone action is absent. This review highlights the importance of specific steroid-inactivating enzymes in the control of target cell sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Metal ions and hydroxyl radicals are thought to be responsible for oxidative damage to macromolecules such as DNA or lipids (44,45). Conjugation of estrogens makes them water soluble to be readily excreted or much more lipophilic to confer longer half-lives than the parent estrogens (46)(47)(48). It has been reported that these metabolic conjugation reactions play a critical role in deactivation of the redox active estrogen metabolites and marked reduction of the classical estrogenic activities of the parent estrogens (49,50).…”
Section: Metabolism Of Estrogenmentioning
confidence: 99%
“…Metal ions and hydroxyl radicals are thought to be responsible for oxidative damage to macromolecules such as DNA or lipids (44,45). Conjugation of estrogens makes them water soluble to be readily excreted or much more lipophilic to confer longer half-lives than the parent estrogens (46)(47)(48). It has been reported that these metabolic conjugation reactions play a critical role in deactivation of the redox active estrogen metabolites and marked reduction of the classical estrogenic activities of the parent estrogens (49,50).…”
Section: Metabolism Of Estrogenmentioning
confidence: 99%
“…UGT2B15 is expressed in luminal cells of the prostate, where DHT is formed, whereas, UGT2B17 is expressed in basal cells of the prostate, where dehydroepiandrosterone is converted into ADT and 3α-Diol [14]. In addition to facilitating the excretion, glucuronidation of androgens mediated by UGT2B15 and UGT2B17 in the prostate results in irreversible steric hindrance of androgens and abolishes the affinity of androgens to AR [15,16]. UGT2B15 and B17 are critical enzymes for the local inactivation of androgens.…”
Section: Introductionmentioning
confidence: 99%
“…They grow independent of progesterone which is known as an important regulatory factor of oxidative 17 -HSD activity in vivo (Tseng & Gurpide 1974, 1975, 1979. Progesterone stimulates the expression of 17 -HSD1 (Poutanen et al 1990, 1992, Mäentausta et al 1993, of 17 -HSD2 (Casey et al 1994) as well as that of 17 -HSD4 (Kaufmann et al 1995). With these characteristics of the cell lines in mind, they represent an appropriate model to study the regulation of 17 -HSD isozymes independent of progesterone.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, oxidative 17 -hydroxysteroid dehydrogenase (17 -HSD) enzyme activity can control the occupancy of the estrogen receptor (Gurpide & Marks 1981; for review see Roy 1992, Penning 1997, Peltoketo et al 1999a. This is a prerequisite for the adequate differentiation of the endometrium in the secretory phase of the menstrual cycle.…”
Section: Introductionmentioning
confidence: 99%